Developing the menstrual justice agenda: insights from a mixed method study in the mid-western region of Nepal - Fran Amery; Melanie Channon; Mahesh C. Puri; Jennifer Thomson (Sexual and Reproductive Health Matters)
This article develops the concept of “menstrual justice”. The legal scholar Margaret E. Johnson has developed an expansive approach to menstrual justice incorporating rights, justice, and a framework for intersectional analysis, with a focus on the US. This framework provides a welcome alternative to the constrictive and medicalised approaches often taken towards menstruation. However, the framework is silent on several issues pertaining to menstruation in Global South contexts. This article therefore develops the concept of menstrual justice in order to extend its relevance beyond the Global North. It presents the findings of mixed-methods research conducted in April 2019 in the mid-western region of Nepal, particularly concerning the practice of chhaupadi, an extreme form of menstrual restriction. We conducted a quantitative survey of 400 adolescent girls and eight focus group discussions, four with adolescent girls and four with adult women. Our findings confirm that dignity in menstruation requires addressing pain management, security issues, and mental health, plus structural issues including economic disadvantage, environmental issues, criminal law, and education.